تحليل العلاقة بين الاعتمادات المستندية والتجارة الخارجية واثرها على تحقيق التنمية الاقتصادية في العراق - خليل, زياد خلف; عبودي, نورة نهاد (Journal of Economics and Administrative Sciences, 2017)
The aim of the research is to clarify the importance of documentary credits in foreign trade and especially their impact on the balance by limiting imports we highlighted the reality of documentary credits in Iraq and the accompanying changes and developments highlighted the indicators of foreign trade and finding solutions for harmonizing the fund Documentary and trade balance in order to achieve long term economic development.The local banks are urged to restore the documentary credit system despite the backwardness and primitive methods used. The documentary credits have increased especially in the last years of the study period. The advantages of the documentary credits have not been used to limit these imports and support the economic development process .